2020
DOI: 10.1016/j.trc.2019.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Integer Programming models for planning maintenance at offshore wind farms under uncertainty

Abstract: We introduce the Stochastic Maintenance Fleet Transportation Problem for Offshore wind farms (SMFTPO), in which a maintenance provider determines an optimal, medium-term planning for maintaining multiple wind farms while controlling for uncertainty in the maintenance tasks and weather conditions. Since the maintenance provider is typically not the owner of a wind farm, it needs to adhere minimum service requirements that specify the required service. We consider three of such settings: 1) perform all maintenan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Shamsaei [10] mentioned that MIP is simpler, faster and more effective than other methodologies such as heuristics and meta-heuristics for industrial systems problems, like the proposed case study. This approach is also strengthened by Schrotenboer [18], who demonstrated that MIP could be successfully used to optimize maintenance equipment under operational uncertainties.…”
Section: Methodsmentioning
confidence: 97%
“…Shamsaei [10] mentioned that MIP is simpler, faster and more effective than other methodologies such as heuristics and meta-heuristics for industrial systems problems, like the proposed case study. This approach is also strengthened by Schrotenboer [18], who demonstrated that MIP could be successfully used to optimize maintenance equipment under operational uncertainties.…”
Section: Methodsmentioning
confidence: 97%
“…Irawan et al 34 performed optimization for uncertainty reduction in routing for an OWF. Schrotenboer et al 35 Researchers also studied other processes directly or indirectly connected to OWF such as port suitability assessment, 87,88 selection of suitable maintenance strategy, 89 challenges of power integration, 90,91 and reviewed structures. 92,93 Some scholars worked on fault detection, 94,95 maintenance organization support model, 96 mixed-integer linear programming, 97 supply chain, 98,99 season-dependent CBM, 100 and three Echelon supply chain.…”
Section: Stochastic Modelsmentioning
confidence: 99%
“…In our experiments, we fitted daily wind speeds for each month of the year independently, similar as in Schrotenboer et al (2020). The fitted parameters are given in Table A…”
Section: Appendix a Wind Distributionsmentioning
confidence: 99%